2016
DOI: 10.1177/1096348016654973
|View full text |Cite
|
Sign up to set email alerts
|

Why Investing in Diversity Management Matters: Organizational Attraction and Person–Organization Fit

Abstract: Corporate investments in diversity management programs have increased over the past two decades. Across two samples, the current study used experimental methods to examine if organizational attraction and person-organization fit (P-O fit) are influenced by corporate investment in diversity management. In Study 1, 132 hotel managers read about a hotel company that either invested in diversity management programs or removed their investment. In Study 2, 159 hospitality students on the job market read about a hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 89 publications
0
29
0
Order By: Relevance
“…First, despite theory that suggests that employee support is an important factor for the efficacy of diversity management (Avery, 2011; Yang & Konrad, 2011), this is the first known research that explores a method to increase positive attitudes toward diversity management. Study 1 focused on a sample of hotel frontline managers, because the success of diversity management programs is highly contingent on managers (Madera, Dawson, & Neal, 2016; Yang & Konrad, 2011). Frontline managers play an important role in the effectiveness of diversity management because diversity management often focuses on reducing discrimination in employment decisions that are typically made by frontline managers, such as selecting, promoting, and developing employees.…”
Section: Discussionmentioning
confidence: 99%
“…First, despite theory that suggests that employee support is an important factor for the efficacy of diversity management (Avery, 2011; Yang & Konrad, 2011), this is the first known research that explores a method to increase positive attitudes toward diversity management. Study 1 focused on a sample of hotel frontline managers, because the success of diversity management programs is highly contingent on managers (Madera, Dawson, & Neal, 2016; Yang & Konrad, 2011). Frontline managers play an important role in the effectiveness of diversity management because diversity management often focuses on reducing discrimination in employment decisions that are typically made by frontline managers, such as selecting, promoting, and developing employees.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent report of PricewaterhouseCoopers (2015) showed that 86% of female and 74% of male millennials consider employers' policies on diversity, equality, and inclusion when deciding which company to work for. In addition, other studies have found that merely stating that diversity is valued positively affects organizations' perceived attractiveness among prospective employees (Madera et al., 2016; Ng & Burke, 2005; Rau & Hyland, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, customized and relevant recruitment messages based on applicant preferences are more likely to attract applicants that are a better fit to the organization. Job seekers perceptions of fit with jobs and organizations are based on individual differences (based on their personal values and identities) (Madera et al, 2018); and these individual differences can be taken into consideration in an organization’s recruitment efforts. The findings of these studies highlight the importance and consideration of judgments of subjective fit paralleling judgments of objective fit among applications.…”
Section: Discussionmentioning
confidence: 99%
“…Signals are often observable or confirmable, and applicants often use information from an organization’s website as signals of what type of organization they are applying to and what the job requires in regard to KSAs (Celani & Singh, 2011). In addition, previous literature suggests human resource management signaling on company websites influences recruitment trends (Chang & Chin, 2018), attraction, and attitudes (Gregory et al, 2013) as well as diversity management (Madera et al, 2018). Therefore, signaling theory provides a theoretical rationale for how companies can leverage their websites to communicate their values and perceived fit to prospective applicants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation